The Evaluation of Medicolegal Aspects of the Child Death Aging From 0 to 5 Years - İnanıcı, Mehmet Akif; Birgen, Nur (The Bulletin of Legal Medicine, 2001)
In our study, among the autopsy reports of the Morgue Department of the Council of Forensic Medicine beetween 1996 and 1998, the reports of 146 cases, aging from 0 to 5 years, were retrospectively investigated. 62 (42,5%) of the cases were female, 83 (56,8%) male. The main manner of death was accident in 36 (24,6%) cases, followed by natural deaths in 33 (22,6%) cases and homicide in 10 (6,9%) cases. The manner of death of 67 (45,9%) cases was unknown. According to the cause of death, pneumonia was the major cause (16,4 %), followed by CO intoxication (11,0 %). While the cause of death of 15 (10,3%) cases were undetermined, the autopsy reports of 48 (32,9%) cases were referred to the Specialization Boards in order to determine the cause of death. This study states that sufficient and detailed scene investigation and postmortem examination are very important in determining the cause and the manner of death.Keywords: Childhood death, cause of death, manner of death
Keywords: childhood death; cause of death; manner of death